Strategic Model in Increasing the SMEs Competitive Advantage in South Sulawesi - Nohong, Mursalim; Sanusi, Abdullah; Nurqamar, Insany Fitri; Harun, Suriadi (UI Scholars Hub, 2018)
The study of SMEs development has become an interesting issue in the field of education including because of its great contribution to society and nation. The research objectives are to describe 1) the effect of government intervention toward the increase of Small and Medium Enterprises (SMEs) innovation capabilities and competitive advantage in South Sulawesi; 2) the effect of non-market capabilities toward non market strategies and competitive advantage of SMEs in South Sulawesi; 3) the effect of non-market capabilities toward government intervention. The data used is the primary data which was obtained from interviews with 40 respondents in Makassar, Parepare, Sidenreng Rappang and Bantaeng. The sample from which data collection done is selected using purposive sampling method. Results are presented in descriptive and inferential statistics. The research results show that innovation, government intervention, nonmarket strategies and capabilities are prerequisite to improve SMEs competitiveness. In addition, the small businesss competitiveness will significantly change when the innovations undertaken are influenced by government intervention.